Social and Theological Adaptation of Minority Groups in Islamic Religious Education Learning in Schools - Muh. Azkar (Lembaga Bale Literasi, 2024)
This article aims to understand the social and theological adaptations of a minority group within the context of Islamic Religious Education in schools. The study employs a constructivist paradigm and a qualitative phenomenological approach. Data were collected through observation, in-depth interviews, and document analysis. The research subjects were Ahmadi students in Lombok. Data analysis involved several stages: repeated reading, initial note-taking, theme development, identifying inter-theme relationships, examining other cases, and seeking common patterns across cases. The findings indicate that this minority group adapts well socially during Islamic Religious Education lessons without feeling ashamed of their Ahmadi identity. Furthermore, the Ahmadi minority group demonstrates theological adaptation by accepting the instructional material, even when it involves beliefs that differ from those of the majority students. Beyond classroom learning, Ahmadi students also actively participate in school activities. These experiences are interpreted as acts of obedience to teachers and school regulations, a means to avoid conflict, a way to achieve academic success, and a method for expanding their knowledge.